Pengaruh Modal Intelektual, Semangat Kerja dan Komitmen Terhadap Kinerja Pegawai Pada Biro Tata Usaha dan Protokol Sekretariat Jenderal Kementerian Pertahanan Republik Indonesia - Agus Wijaya, Agustinus; Supriyatno, Budi; Hariyadi, Ade Reza (FIA Unkris Press, 2024)
The aim of this research is to determine and analyze the influence of intellectual capital, work enthusiasm and commitment partially and jointly on employee performance at the Administration and Protocol Bureau of the Secretariat General of the Indonesian Ministry of Defense. The research method uses a survey with a descriptive quantitative approach. The sampling technique is the Simple Random Sampling technique. The total sample was 59 respondents. Based on the research results, it was found that: a) The results of partial hypothesis testing, intellectual capital has a significant effect on employee performance at the Administration and Protocol Bureau of the Secretariat General of the Ministry of Defense of the Republic of Indonesia. b) Results of partial hypothesis testing, work morale has a significant effect on employee performance at the Administration and Protocol Bureau of the Secretariat General of the Ministry of Defense of the Republic of Indonesia. c) The results of partial hypothesis testing that commitment has a significant effect on employee performance at the Administration and Protocol Bureau of the Secretariat General of the Ministry of Defense of the Republic of Indonesia. d) Results of simultaneous hypothesis testing: intellectual capital, work enthusiasm and commitment together have a significant effect on employee performance at the Administration and Protocol Bureau of the Secretariat General of the Ministry of Defense of the Republic of Indonesia